2018
DOI: 10.22159/ajpcr.2018.v11i8.26636
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dillenia Indica L. Against Oxidative Stress-Induced Cardiomyopathy on Alloxan-Induced Diabetes Mice Model

Abstract: Objective: The aim of the present study is to investigate the antihyperglycemic and antioxidative properties of Dillenia indica fruits.Methods: Aqueous fruit extract and methanolic fruit extract (MFE) were prepared, and preliminary phytochemical screening was carried out. Diabetic mice were prepared with alloxan (150 mg/kg) body weight (b.w.). Antihyperglycemic study of short duration was carried out with doses (150–550) mg/kg b.w. of MFE in diabetic mice. Antioxidant enzymes (superoxide dismutase, catalase, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Hyperglycemia causes an increase in glucose flux and other sugars through the polyol pathway, thereby increasing advanced glycation end-products (AGEs) intracellularly [45]. Evidence from various studies also indicated that hyperglycemia and elevated levels of AGEs may enhance reactive oxygen species (ROS) and oxidative stress [4648]. Alcohol and hydroalcohol extract of Dillenia indica was evaluated for its in vitro inhibitory activity against AGE formation by using bovine serum albumin.…”
Section: Dillenia Indica As Antidiabetic: Molecular Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperglycemia causes an increase in glucose flux and other sugars through the polyol pathway, thereby increasing advanced glycation end-products (AGEs) intracellularly [45]. Evidence from various studies also indicated that hyperglycemia and elevated levels of AGEs may enhance reactive oxygen species (ROS) and oxidative stress [4648]. Alcohol and hydroalcohol extract of Dillenia indica was evaluated for its in vitro inhibitory activity against AGE formation by using bovine serum albumin.…”
Section: Dillenia Indica As Antidiabetic: Molecular Mechanismsmentioning
confidence: 99%
“…The methanolic fruit extract (MEF) of Dillenia indica was administered to mice at a dose range of 150–550 mg/kg b.w. The study found that 350 mg/kg dose of MFE was found to be effective in alleviating the blood glucose level as well as oxidative stress [48]. Another study also showed that alcoholic extract of Dillenia indica (DAE) and isolated compound, chromane, showed high scavenging activity towards hydroxyl radical and superoxide anion, along with high reducing power activity [26].…”
Section: Dillenia Indica As Antidiabetic: Molecular Mechanismsmentioning
confidence: 99%
“…[4,5] Some known flavonoids were identified in the fruit extract, being evidenced as responsible for xanthine inhibitory properties, [6] in addition to proanthocyanidins with potent antioxidant activity. [7] Several recent studies with fruit extracts of D. indica have evidenced diverse in vivo medicinal properties, including attenuation of cardiomyopathy, [8] hyperglycemia and modulation of oxidative stress and apoptosis, [9] and prevention of sucrose-induced fatty liver and biochemical alterations. [10] Moreover, fruit extracts have been reported for their cytotoxic effects against oral squamous cell carcinoma [11] and, antibacterial and antimutagenic properties (Jaiswal, S.; 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous research groups have conducted thorough pharmacogenetic and phytochemical studies in light of the plant's therapeutic potentials. [84][85][86] Its fruits are of particular interest, and are known to possess anti-oxidant [87] and anti-leukemic [88] activities, which are attributed respectively to the rich phenolic contents and the presence of betulinic acid. The acidic catalyst properties of the aqueous extract are demonstrated by its pH, which ranges between 3 and 4.…”
Section: Introductionmentioning
confidence: 99%
“…Elephant apple, scientifically known as Dillenia indica , is a highly valued medicinal plant that is often found in the northeast of India and the foothills of the Himalayas. Numerous research groups have conducted thorough pharmacogenetic and phytochemical studies in light of the plant‘s therapeutic potentials [84–86] . Its fruits are of particular interest, and are known to possess anti‐oxidant [87] and anti‐leukemic [88] activities, which are attributed respectively to the rich phenolic contents and the presence of betulinic acid.…”
Section: Introductionmentioning
confidence: 99%